HISTOLOGICAL AND HISTOMORPHOMETRIC STUDY OF RETINA IN PIGEON AND DUCK - Mohammed A. Ali (Basrah Journal of Veterinary Research)
ABSTRACT The eye ball ( globe) comprises Three concentric layers. ( The fibrous tunic, The vascular tunic, and the nervous tunic. And the nervous tunic the deepest layer of the eye ball is the internal (nervous ) tunic or retina. The study aimed to determine the histological structure of retina. The histological and histomorphometric Study Showed The retina as representing internal Tunica ( Nervous). And show That retina in pigeon and duck haves many layers ( ten layers); One of these is the photoreceptor Layer , In which are found the specialized neural receptor cells of the visual system, The rods and cones are more dominant while the rods are most in photoreceptors layer also the measurement of retina is smallest than in the center ( middle) and the measuring of rods and cones layers in pigeon, smallest than in duck.